Analysis of Underwriter Performance in Determining Prospective Participants in Motorkoe Insurance Products - Irna Ardilla; Yusrizal Yusrizal (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The insurance industry is a form of a business entity engaged in services that has a social role as well as an economic role. In order to realize maximum results, every insurance industry certainly requires superior human resources to develop and market its processes. This also cannot be separated from the role and performance of the Underwriter, who plays an important role in evaluating whether prospective insurance members are acceptable or not in order to meet the goals of the insurance industry. According to research findings, the underwriter’s performance plays an important role in determining prospective members of the Motorkoe insurance process, namely: collecting customer information, carrying out data verification, carrying out appraisals, and submitting company decisions. This paper aims to find out how the underwriter performs in determining potential participants in Motorkoe insurance products and the factors that influence underwriter performance in Motorkoe insurance products. This research was conducted at PT. Bumida 1967 Medan branch. This type of research uses a qualitative approach and a descriptive method. While the data collection techniques used by researchers are interviews, observation as well as documentation. The results of this study describe that performance in determining potential participants in Motorkoe insurance products has been running as efficiently as possible. Judging from the underwriting surplus, it can be used as a reserve, thereby increasing public interest in general insurance. The surplus results obtained by Bumida Medan Branch in the Motorkoe process in 2022 amounted to 37,080,000, 00 with 181 processes in the Motorkoe process worth 51,080,000.00 with 1 claim member of 14,000,000.00 and with a Motorkoe total loss ratio which embodies the figure of -27%. The factors that influence the underwriter’s performance are: 1) Age, 2) Work motivation, 3) Health, 4) Targets set by the company, and 5) Understanding of the activities carried out.